The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1080/14640749508401384
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Aspects of the Base-rate Fallacy

Abstract: An investigation was made of the role played by verbal structure in the problems used to study the base-rate fallacy, which has traditionally been attributed to the role of heuristics (e.g. causality, specificity). It was hypothesized that elements of the verbal form of text problems led to a misunderstanding of the question or the specific information, rendering obscure the independence of the sets of data (specific information is obtained independently from the base rate). Nine texts were presented to variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
64
1
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(66 citation statements)
references
References 19 publications
0
64
1
1
Order By: Relevance
“…Furthermore, this explanation conflicts with the sample-space account because Macchi's suggestion that participants' interpretations [i.e., formulation (2)] rely on the sample space defined by feature D. Yet, according to the sample-space explanation, this is an unnatural and unlikely basis for probabilityjudgments. Finally, even though our formulation of the diagnostic information was in line with Macchi's (1995) recommendations for reducing the inverse fallacy, we still found that 51% of participants made almost all their judgments in accordance with the inverse fallacy.…”
Section: Theoretical Implicationsmentioning
confidence: 58%
See 3 more Smart Citations
“…Furthermore, this explanation conflicts with the sample-space account because Macchi's suggestion that participants' interpretations [i.e., formulation (2)] rely on the sample space defined by feature D. Yet, according to the sample-space explanation, this is an unnatural and unlikely basis for probabilityjudgments. Finally, even though our formulation of the diagnostic information was in line with Macchi's (1995) recommendations for reducing the inverse fallacy, we still found that 51% of participants made almost all their judgments in accordance with the inverse fallacy.…”
Section: Theoretical Implicationsmentioning
confidence: 58%
“…This tendency has been alternatively labeled the conversion error (Wolfe, 1995), the confusion hypothesis (Macchi, 1995), the Fisherian algorithm (Gigerenzer & Hoffrage, 1995), and the inverse fallacy (Koehler, 1996a). In the present article, we adopt Koehler's term to refer to the tendency for judges to confuse any of participants can use when they estimate posterior probabilities (see, e.g., Gigerenzer & Hoffrage, 1995), the inverse fallacy is often the most frequent error observed.…”
Section: The Inverse Fallacymentioning
confidence: 99%
See 2 more Smart Citations
“…It would appear that the natural frequency format makes directly available to participants the information they need to make likelihood estimates, rather than forcing them to derive the information from base rates and rates of witness accuracy. Similarly Macchi (1995Macchi ( , 2000 has argued that making transparent the conditional probabilities inherent in base rate problems and the links among the pieces of information presented in problems may minimize base rate neglect. Certainly, it is desirable to present information in the most transparent and usable manner possible; however, much of the statistical information to which people are exposed in daily life is in the form of probabilities.…”
mentioning
confidence: 99%